Environmental perception of students from colégio de aplicação-ufrr about enronmental impacts in urban river basin of boa vista/rr - Rosa da Silva, Carmem Lúcia (Geosaberes, 2017)
This article describes my teaching practices along with the related experiment to my doctoral project, a requirement for approval in disciplines Teaching Stage II and III of the Doctorate Degree course in Geography, Federal University of Ceará. In doctoral thesis, I intend to evaluate the environmental awareness of students of the 1 st Year High School CAp/UFRR on environmental degradation processes of the hydrographic basin of Frasco stream. However, this experiment aims to diagnose and analyze the level of perception and prior sensitization of students. For data collection it was used questionnaire and the analysis of the results showed that the students realize the integrated landscape mode, posing themselves as the middle part. The result showed that the watershed was not understood as an "open system". Around 40% of the students believe the hydrographic basin just as an área. It is clear the difficulty they have in understanding basin as a geosystem. The continuity of this work that permeates the construction of the thesis aims to involve students participating in new methodologies, and increase the perception that students have on the environment and sensitize them to the need for a new paradigm, with new values ​​and attitudes to sustainability environmental.
Keywords: Experiência Ambiental: Prática Pedagógica; Sensibilização.